TAHAP AWAL MENJELANG PELAKSANAAN PROSESI MOME’ATI MASYARAKAT GORONTALO - Elan Halid; Hasmi Novianti (Universitas Andalas, 2017)
This research is based on the cultural tradition of Gorontalo people who always uphold the customs of their ancestors from generation to generation. The ceremony will not be separated from every individual wherever located. The ceremony is different from each other. In Gorontalo for example, the ceremony mome'ati (pembeatan) is still very thick and still often done. This is because, it has become a woman's tradition when entering adolescence to make pembeatan or agreement. Settlement can also be made before the marriage contract. This mome'ati process is different from other traditional ceremonies, even a very unique ceremony in Gorontalo Province, in contrast to traditional ceremonies that exist in other areas. The momeati customs, which are preceded by the stages of activity, molungudu, momonto, mopoduta'a to hipe, mome'ati and mohatamu. The procession of mome'ati is a consequence of the family / parents, fostering the daughter in order to keep the inner and outer purity, with the knowledge of self-cleansing, and the guarding of her holiness in her life. The stage of the ceremony in the event / aspect of birth and youth, which is hereditary applied by the people of Gorontalo tribe. Based on the background that researchers feel interested in doing research on the early stage ahead of the implementation procession mome'ati Gorontalo people. The method used in this research is descriptive method and semiotic approach. Data were collected through observation, interview and documentation techniques.Keywords: The nature of mome'ati, mome'ati procession, and the people of Gorontalo.